2020
DOI: 10.1186/s40461-020-00091-y
|View full text |Cite
|
Sign up to set email alerts
|

How do the digital competences of students in vocational schools differ from those of students in cooperative higher education institutions in Germany?

Abstract: Digital skills are thought to be a key competence of the twenty-first century. With the rapid growth of internet and communication tool (ICT) usage among both students and teachers, cooperative (co-op) education programmes, like other educational institutions, face the challenge of integrating and supporting digital skill development. However, little is known about how these skills are developed prior to entering cooperative education programmes. Against this background, a sample of 893 freshers, ranging from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 38 publications
6
31
1
1
Order By: Relevance
“…The results above can be considered as consistent with the research [16], which has shown that digital literacy is influenced by education. In our case, it is also influenced by education, but from the point of view of the certain specialization of the study programme, the level and form of study.…”
Section: Fig 2 Cluster Analysis Of Competencessupporting
confidence: 91%
See 3 more Smart Citations
“…The results above can be considered as consistent with the research [16], which has shown that digital literacy is influenced by education. In our case, it is also influenced by education, but from the point of view of the certain specialization of the study programme, the level and form of study.…”
Section: Fig 2 Cluster Analysis Of Competencessupporting
confidence: 91%
“…The element that would be separated from the group last if the set number of clusters was enlarged was always chosen. The competences were grouped into the following six clusters: Basic (1,2,4,7,8,9,13,17,18,19,20,21,22,23,24,25,27); Advanced (10,11,12); Personal information management ( 14); E-forms (26); Operating system administration (3,6,15,16); Operating system control (5).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research also points out that the patterns of digital divide transgress into VET and higher education (Murray & Pérez, 2014;Wild & Schulze Heuling, 2020b). Therefore, we will also pay attention towards the question if the skills gap among students related to SES and gender reproduces in this study.…”
Section: The Digital Dividementioning
confidence: 94%